2023
DOI: 10.3389/fneur.2023.1137958
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ganglionic acetylcholine receptor antibodies in functional neurological symptom disorder/conversion disorder

Abstract: ObjectiveAutoimmune autonomic ganglionopathy (AAG) is a rare disorder characterized by autonomic failure associated with the presence of anti-ganglionic acetylcholine receptor (gAChR) antibodies; however, several studies have reported that individuals with anti-gAChR antibodies present with central nervous system (CNS) symptoms such as impaired consciousness and seizures. In the present study, we investigated whether the presence of serum anti-gAChR antibodies correlated with autonomic symptoms in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Studies on anti-N-methyl-D-aspartate receptor encephalitis potential relapses are limited and opposed, data on autoimmune autonomic ganglionopathy and myalgic encephalomyelitis/chronic fatigue syndrome are again limited, and so are data on autoimmune hypophysitis—with a case report showing high CRP possibly in relapse [ 749 , 750 , 751 , 752 , 753 ]. Moreover, CRP can be elevated in Guillain–Barré syndrome, in which it can possibly be a risk factor for disease severity, particularly in adults [ 754 , 755 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…Studies on anti-N-methyl-D-aspartate receptor encephalitis potential relapses are limited and opposed, data on autoimmune autonomic ganglionopathy and myalgic encephalomyelitis/chronic fatigue syndrome are again limited, and so are data on autoimmune hypophysitis—with a case report showing high CRP possibly in relapse [ 749 , 750 , 751 , 752 , 753 ]. Moreover, CRP can be elevated in Guillain–Barré syndrome, in which it can possibly be a risk factor for disease severity, particularly in adults [ 754 , 755 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…Recent findings suggest that FND is associated with neuroendocrine and immune abnormalities [8]. Specifically, patients with this disorder show blunted morning cortisol secretion [911], alterations in peripheral inflammatory markers, such as C-reactive protein, interferon-gamma, interleukin-6, and tumor necrosis factor-alpha [12–14], and presence of anti-ganglionic acetylcholine receptor antibodies associated with autonomic dysfunction [15,16]. Furthermore, a recent hypothesis-free genome-wide epigenetic study identified methylomic changes at the level of multiple immune-related pathways in individuals with FND with and without history of childhood abuse [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that FND is associated with neuroendocrine and immune abnormalities [8]. Specifically, patients with this disorder show blunted morning cortisol secretion [9][10][11], alterations in peripheral inflammatory markers, such as C-reactive protein, interferon-gamma, interleukin-6, and tumor necrosis factor-alpha [12][13][14], and presence of antiganglionic acetylcholine receptor antibodies associated with autonomic dysfunction [15,16].…”
Section: Introductionmentioning
confidence: 99%